Pornografi Sebagai Sebuah Realitas Sosial (Kajian dari Aspek Filsafat Sosial dan Agama) - Djakfar, Muhammad; Rasmianto, Rasmianto (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2003)
Pornography and porno-action are the two words commonly heard and often become the community discourse. Even today the porno-action, which exploits the body of human being-especially the women-, become worse and is covered nicely as marketable entertainment business. It is believed that the growth of pornography and porno-action is not caused by a single Variable but is supported by other variables usually done by the artists as public figure and published by mass media. According to social philosophy paradigm, the great amount of pornography and porno-action today has clearly destroyed the perfect order of social structure. While according to Islam, it depends on how deep the subject's belief to the religious norm is. The more firmly they hold the religious values, the more slowly pornography and porno-action develop, so that the social structure is not very much disturbed. Therefore, the instruments to be applied to slow down the development of pornography and porno-action are establishing social awareness, as well as realizing the regulations for anti-pornography which function as efforts of prevention and cure.